Are awe‐prone people more curious? The relationship between dispositional awe, curiosity, and academic outcomes. Issue 4 (10th December 2019) - Anderson, Craig L.; Dixson, Dante D.; Monroy, Maria; Keltner, Dacher
Abstract: Objective: Guided by a functional account of awe, we aimed to test the hypothesis that people who often feel awe are also more curious (Studies 1 and 2), and that this relationship in turn relates to academic outcomes (Study 3). Method: In Study 1 ( n  = 1, 005), we used a self‐report approach to test the relationship between dispositional awe and curiosity. In Study 2 ( n  = 100), we used a peer‐report approach to test if participants' dispositional awe related to how curious they were rated by their friends. In Study 3, in a sample of 447 high school adolescents we tested if dispositional awe related to academic outcomes via curiosity. Results: We found that dispositional awe was positively related to people's self‐rated curiosity (Study 1) and how curious they were rated by their friends (Study 2). In Study 3, we found that dispositional awe was related to academic outcomes via curiosity. Conclusions: We conclude that among the seven positive emotion dispositions tested, awe was related to unique variance in curiosity, and this link in turn predicted academic outcomes. This work further characterizes awe as an epistemic emotion and suggests that activities that inspire awe may improve academic outcomes.